Efektivitas Penggunaan Media Pembelajaran Permainan Tradisional Gobak Sodor Untuk Meningkatkan Kemampuan Motorik Kasar Pada Siswa Tunagrahita Ringan Di SLB YKPC GBKP Alpha Omega (Universitas Negeri Semarang, 2021)
Background:(1) Physical education is a part of education that affects the potential of students in terms of cognitive, affective, and psychomotor which are inseparable from education in general. (2) Gross motor skills are abilities related to the movement of large muscles in controlling body movements through locomotor, non-locomotor, and manipulative abilities. (3) The gobak sodor game can develop children's gross motor skills. Research Questions: (1) Is there an effect of the traditional Gobak Sodor game on pace? (2) What influence does the traditional game of Gobak Sodor have on agility? (3) What effect does the traditional Gobak Sodor game have on reaction speed?. The research method used was an experiment with a